Aldehyde-functional copolymers based on poly(2-oxazoline) for post-polymerization modification. (January 2015) - Legros, Camille; De Pauw-Gillet, Marie-Claire; Tam, Kam Chiu; Lecommandoux, Sébastien; Taton, Daniel
Graphical abstract: Highlights: Copolyoxazolines with protected or unprotected aldehyde handles were synthesized. Post polymerization reactions led to graft or cross-linked materials. Hydrogels prepared from a dihydrazide crosslinker proved pH-responsive. Copolyoxazolines were subjected to an intermolecular self-aldolization reaction. Abstract: Protected and non-protected homopolymers and related statistical copolymers based on poly(2-oxazoline) were synthesized by cationic ring-opening (co)polymerization, using a protected aldehyde 2-oxazoline monomer, namely, 2-[3-(1, 3)-dioxolan-2-ylpropyl]-2-oxazoline (DPOx). The (co)polymer precursors were subsequently used as reactive platforms enabling the synthesis of miscellaneous derivatives, including graft and cross-linked copoly(2-oxazoline)s. Aldehyde-functional (co)polymers were first reacted with mono- or bi-functional amino- and hydrazido-containing reagents, forming grafted copolymers or chemically cross-linked networks, respectively. The latter compound consisting of hydrazone-type linkages formed hydrogels that could be slowly degraded at physiological pH over 3 days, but be readily cleaved in a more acidic environment (pH = 3). Aldehyde-containing (co)polymers were also found to be subjected to an intermolecular self-aldolization reaction under acidic conditions, leading to branchings and ultimately to the formation of dense 3D-networks.